HUBUNGAN INDEKS MEROKOK BRINKMAN DAN AKTIFITAS FISIK PADA MASA COVID-19 DENGAN TEKANAN DARAH DI KOTA PALANGKARAYA: THE RELATIONSHIP BETWEEN THE BRINKMAN SMOKING INDEX AND PHYSICAL ACTIVITY DURING COVID-19 WITH BLOOD PRESSURE IN PALANGKARAYA CITY - Balyas, Abi Bakring; Indra Permana, Galih (ITKES Wiyata Husada Samarinda, 2024)
Hypertension is a disease characterized by an increase in systolic blood pressure above 140 mmHg and diastolic blood pressure above 90 mmHg. This study aims to prove the existence of a relationship between physical activity and the degree of smoking and systolic and diastolic blood pressure. The research method used was a cross-sectional design with a sample size of 51 non-obese adult men. Sample selection used purposive techniques. Physical activity was measured by completing the International Physical Activity Questionnaire. The degree of smoking obtained was measured using the Brinkman Index. The results showed that there was a significant relationship between the Brinkman smoking index and systolic blood pressure and diastolic blood pressure as well as between physical activity and systolic blood pressure, but there was no significant relationship between physical activity and diastolic blood pressure.